Aquila's Roads: Connecting Paphlagonian Spaces - Ching-yuan Wu (Gephyra)
This study examines the socio-political landscape of the ancient city of Amastris (modern Amasra) through the lens of its road infrastructure, with a particular focus on the construction and significance of Aquila’s roads. Situated in the challenging terrain of northern Anatolia’s Küre Mountains, Amastris served as a vital maritime hub, linking diverse inland and coastal communities within Paphlagonia. Employing a multidisciplinary approach that integrates ancient literary analysis, archaeological evidence, geospatial modeling, and modern photogrammetry, this paper reconstructs the network of primary and secondary Roman roads emanating from Amastris. The research highlights the dual role of these roads in fostering territorial coherence and enhancing regional connectivity, supporting both local autonomy and imperial governance. Key findings demonstrate that Aquila’s roads were not merely infrastructural projects but strategic undertakings that blended private investment with public utility. These projects reflect the intricate interplay between individual agency and state interests in Roman provincial administration. Furthermore, the study explores the broader cultural and economic impacts of road construction on Amastris, illustrating how connectivity shaped civic identity, social integration, and territorial integrity. The paper concludes that Aquila’s road-building initiatives were instrumental in sustaining Amastris’s strategic significance and functionality within the Roman Empire. By examining the dynamic relationship between local and imperial priorities, this study offers insights into how infrastructure functioned as a nexus of governance, economic development, and regional integration in ancient Anatolia.